The Effect of Cucumber Juice Administration on Blood Pressure Reduction in Older Adults Hypertension: A Case Study - Annisa Nur Khasanah; Ida Nur Imamah; Tri Harwanto (Al-Hijrah Indonesia, 2025)
Background: Hypertension remains a leading global public health concern, particularly among older adults. Non-pharmacological interventions, including dietary approaches, are increasingly recognized as complementary strategies for managing blood pressure. Cucumber juice, rich in potassium and water, has been proposed as a natural and accessible adjunctive therapy for hypertension. Objective: This study aimed to evaluate the effect of daily cucumber juice administration on blood pressure reduction in hypertensive patients in RW 07, Purwodiningratan Village, Surakarta City, Indonesia. Methods: A descriptive case study was conducted over seven days (April 27–May 3, 2025), involving two hypertensive respondents aged 45 years or older who were concurrently receiving amlodipine. Cucumber juice (200 mL/day) was administered daily, and blood pressure was measured before and two hours after consumption using a digital sphygmomanometer. Data were analyzed descriptively by comparing pre- and post-intervention blood pressure categories. Results: Respondent 1’s blood pressure decreased from 168/100 mmHg (Stage 2 hypertension) to 127/84 mmHg (normal) after seven days. Respondent 2’s blood pressure improved from 186/119 mmHg (Stage 3 hypertension) to 148/90 mmHg (Stage 1 hypertension). Both cases demonstrated a consistent daily decline in systolic and diastolic values throughout the intervention period. Conclusion: The daily administration of cucumber juice contributes to a significant reduction in blood pressure in hypertensive patients when used in conjunction with standard pharmacological treatment. These findings support the potential of cucumber juice as a feasible, low-cost non-pharmacological adjunct in community-based hypertension management. Further research with larger samples and controlled designs is recommended to validate these preliminary results.